(untitled) (CAHIERS MAGELLANES-NS, 2024)
The molecular docking interactions between HIV-1 reverse transcriptase (RT) and two novel compounds, Compound-1 (C-1) and Compound-2 (C-2) of Withania somnifera, were investigated to assess their potential as inhibitors of the enzyme. Compared to the standard drug Efavirenz, both C-1 and C-2 exhibited superior binding attributes. C-2 displayed a notably lower binding energy of -7.45 kcal/mol, indicating a stronger binding potential. It formed six hydrogen bonds, double the amount established by Efavirenz, highlighting the enhanced stability and specificity of the C-2-HIV-1 RT interaction. Furthermore, C-2's interactions with a broader range of hydrophobic amino acids underscored its potential superiority in forming a stable and specific binding complex. Similarly, C-1 exhibited a lower binding energy of -6.69 kcal/mol and formed five hydrogen bonds, in contrast to Efavirenz's two, suggesting a more intricate and stable binding pattern. This enhanced interaction was further emphasized by C-1's engagement in hydrophobic interactions with specific amino acids. The findings collectively indicate that both C-1 and C-2 possess superior molecular docking attributes compared to the standard drug, highlighting their potential as promising inhibitors of HIV-1 RT. These results support the further investigation and development of these compounds as potential anti-HIV agents to advance treatment options for HIV/AIDS.